Impact of post-treatment symptoms on supportive care needs among breast cancer survivors in South Korea - Unhee Kim; Ju-Young Lee (Elsevier, 2023)
Objective: The aim of this study is to investigate the factors influencing the supportive care needs of survivors of breast cancer who have completed major treatment. Methods: A total of 121 survivors of breast cancer from an online community in South Korea participated in this study. The study variables were supportive care needs, physical symptoms, anxiety, and depression. Independent t-tests, one-way Analysis of Variance (ANOVA), Pearson's correlation, and hierarchical regression analyses were performed. Results: The highest rankings of supportive care needs of survivors of breast cancer were medical system and information needs, patient care and support needs, psychological needs, sexual needs, and physical and daily life needs. Hierarchical regression analysis revealed that the participants' supportive care needs were explained by physical symptoms (P ​< ​0.001) and anxiety (P ​< ​0.001), accounting for 52.1% of the variance. Conclusions: Supportive care needs of survivors of breast cancer have a high level of medical system and information needs, and posttreatment conditions are related to high physical symptoms and anxiety. In the future, it will be necessary to identify supportive care needs and apply interventions to reduce their physical symptoms and anxiety.